Innovation in Digital based History Learning through Flipbooks for Elementary School Students in Lembang District - Susilo, Dimas Rachmat; Wiyanarti, Erlina; Mulyana, Agus; Darmawan, Wawan (PrimaryEdu : Journal of Primary Education, 2025)
This study evaluates the effectiveness of using flipbooks as digital-based history teaching materials in elementary schools in the Lembang area. Using a descriptive qualitative approach, this study found that flipbooks can significantly improve students' motivation, engagement, and understanding. The test results showed an increase in students' average scores and critical thinking skills. Despite challenges such as limited technological devices and teacher readiness, proper support allows flipbooks to function effectively in learning. Teachers play an important role as facilitators and innovators in the integration of this technology. These findings indicate the great potential of flipbooks to improve the quality of education, as well as the importance of widespread adoption in other school curricula.